MEASURING THE EFFECT OF CBR AND TCP TRAFFIC MODELS OVER DYMO ROUTING PROTOCOL (Global Journal of Computer Science and Technology, 2011)
A Mobile Ad hoc Network MANET are classified as single or multihop wireless network in which nodes can freely move and dynamically self-organize also the network is highly dynamic in terms of topological changes Mobile nodes can communicate with themselves without any need of predefined infrastructure But due to the dynamic nature of MANETs in terms of mobility and no infrastructure they are provided with limited bandwidth and limited battery power Due to these characteristics the MANETs are best suited for military operations in battlefield grounds Disaster relief and rescue operations Choosing the mobility model is very much crucial for specific application area that represents the moving behaviour of a mobile node that should be realistic Changing the mobility scenario allows changes in routing performance of a routing protocol in terms of routing metrics such as Delays Throughput and Routing Overhead etc within the current application area Main aim of this research paper focus to study the effects of Transmission Control Protocol TCP and Constant Bit Rate CBR from different angles over Dynamic MANET on demand routing protocol known as DYMO in order to find out the performance degradation on the basis of Data packets and Control packets Using the Network Simulator 2 experimental results show that functions of the routing protocol vary across different parameters like sending and receiving ratio of data packets and numbers of Control packets send during the simulation period
Keywords: Ad Hoc network; CBR; DYMO; TCP; MANET; Traffic patterns